The Effect of Profitability, Solvency and Company Size on Audit Delay - Prasetyo, Dwi; Santosa, R. Eri Wibowo Agung; Kristiana, Ida (Economics and Business International Conference Proceeding, 2024)
This study aims to analyze the influence of profitability, solvency, and company size on audit delay in companies listed on the Indonesia Stock Exchange. Using the regression analysis method, this study tests the hypothesis that profitability, solvency, and company size have a significant relationship with audit delay. The data used in this study includes financial statements from a number of companies listed on the Indonesia Stock Exchange. The results show that profitability (ROE) has a positive and significant influence on audit delay, with a calculation value of 3.592 and a significance value of 0.00. This shows that companies with higher profitability levels tend to experience longer audit times. Solvency (Debt Ratio) also showed a positive influence on audit delay, but this effect was not statistically significant with a calculation value of 2.689 and a significance value of 0.08. On the other hand, the size of the company (Total Assets) did not show a significant influence on the audit delay, with a calculation value of -0.078 and a significance value of 0.387. Overall, this study concludes that profitability is an important factor affecting audit delays in companies in Indonesia, while solvency and company size do not have a significant influence. These findings provide new insights for practitioners and researchers to understand the dynamics that affect the audit process in Indonesia. For future research, it is recommended to explore other variables that may affect audit delay and expand the research sample to obtain more representative results.